State domestic anti-corruption policy: history of formation and development - K.M. (Економіка, управління та адміністрування, 2023)
The article deals with issues of the history of the formation and development of state anti-corruption policy in Ukraine. In the process of working out its conceptual aspect, it is proposed to understand the state anti-corruption policy as a set of state management goals, measures, decisions, areas of activity in the field of prevention, counteraction and fight against corruption and the order of their implementation. This approach makes it possible to take into account the already formed principles of public management science. As a result of developing a package of anti-corruption legislation, it is proposed to apply an institutional approach to their formation in the process of determining the target areas of the above-mentioned policy, which, with the necessary differentiation into the relevant subsectors, will allow to maximally cover all spheres of society with anti-corruption measures, the need for which is certainly quite high today, as well as emphasize within the general public administration sector special attention on the public finance management system. In order to develop the theoretical foundations of the state domestic anti-corruption policy, a periodization of its development is proposed, which involves distinguishing the following stages: the birth stage of the state anti-corruption policy (1991-1995); the stage of formation and formation of general provisions of the state anti-corruption policy (1996-2003); the stage of initial implementation of international approaches to state anti-corruption policy (2004-2014); the stage of development of institutional support of state anti-corruption policy and activation of further implementation of international approaches to state anti-corruption policy (2015 - until now). The proposed approach reflects all significant steps on the way to building the national state.